CLASSIFYING EMOTIONS THROUGH ANALYZING NOMINATIONS OF THE CATEGORY EMOTIONS COMPONENTS - Shamaieva, Iulia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The present article focuses on the issue of classifying emotions through analyzing their nominations as names of concepts-components of the verbalized category EMOTIONS to develop an efficient methodology to research this category in the English language and discourse within the framework of cognitive linguistics and linguoculturology. As a result of our studying the seme content of lexemes, nominating the category EMOTIONS, there has been the archiseme ‘feeling experience response’ and the hypersemes ‘stimulus experience’, evaluation’, emergence time as to events’, ‘direction’ revealed, which considerably enhances classification optimization.